International Preferences in Selecting Mates: A Study of 37 Cultures - Buss, D. (Array, 1990)
This study sought to identify the effects of culture and sex on mate preferences using samples drawn world-wide. Thirty-seven samples were obtained from 33 countries located on six continents and five islands (N=9474). Hierarchical multiple regressions revealed strong effects of both culture and sex, moderated by specific mate characteristics. Each culture displayed a unique preference ordering, but there were some similarities among all cultures as reflected in a positive manifold of the cross-country correlation matrix. Multidimensional scaling of the cultures yielded a five-dimension solution, the first two of which were interpreted: traditional vs. modern and valuation of education, intelligence and refinement. Consistent sex differences in value attached to earning potential and physical attractiveness supported evolution-based hypotheses about the importance of resources and reproductive value in mates. Discussion emphasizes the importance of psychological mate preferences for scientific disciplines ranging from evolutionary biology to sociology.